Editorial statement and research ideas for efficiency and anomalies in stock markets - Wing Keung Wong (Economies, 2020)
The Efficient Market Hypothesis states that it is impossible for an investor to outperform the market because all available information is already built into stock prices. However, some anomalies could persist in stock markets while some other anomalies could appear, disappear and re-appear again without any warning. To explore new theories with applications in this direction, in this editorial, we suggest ideas to authors on what types of papers we will accept for publication in the areas of on Efficiency and Anomalies in Stock Markets. We will discuss some papers published in the special issue of Efficiency and Anomalies in Stock Markets.
Keywords: 330; anomaly; applications; finance; market efficiency; stock market